LEARNING AND TEACHING A FOREIGN LANGUAGE VIA THE INTERNET - Mustayeva, Guldora (Журнал иностранных языков и лингвистики, 2023)
In our article, we tend to share our thoughts on the subject. On the eve of the 21st century, I believe there is no other way to learn languages ​​conveniently and understandably for people who are not native speakers than learning over the Internet (IBE). As our lives become computerized day by day, the day when modern technology will replace traditional teaching methods is not far away. While this is an appropriate teaching and learning method, it has side effects in creating a successful teaching/learning environment.